Soil water depletion and recharge under different land cover in China's Loess Plateau. Issue 3 (22nd May 2015) - Fan, Jun; Wang, Quanjiu; Jones, Scott B.; Shao, Mingan
Abstract: Vegetation restoration can greatly influence water infiltration and root water uptake depths in semi‐arid regions. Soil water dynamics within different vegetated/non‐vegetated land cover patterns were studied over time from 2008 to 2013 in an erodible small watershed on the Loess Plateau of China. Results showed that distinct differences in soil water dynamics and water balances existed among different vegetation types. Soil water recharge depths extended deeper than 5 m under bare land and farmland, but introduced forage (alfalfa) and shrub (caragana) species depleted the soil water stores in the 0‐ to 6‐m layers within a few years, prevented deep soil water recharge and exhibited negative water balances. Local food crops can maintain a sustainable soil water balance although there was low productivity. Native grasses should be the best land use type for this region based on the soil water balances observed in this short field study. Because it was difficult to avoid soil desiccation under introduced vegetation, vegetation with high water demands should be combined with shallow rooting plants, and water‐saving methods should be taken into account. Copyright © 2015 John Wiley & Sons, Ltd.